Digital Words of Wisdom? Milia (AppleTree), An Online Platform for Digital Storytelling - Spanoudakis Manolis; Nakou Alexandra; Meliadou Eni; Gouscos Dimitris; Meimaris Michalis (Cultural Science)
This paper introduces Milia (AppleTree), an open online platform for social interactive digital storytelling, which has been developed by the Laboratory of New Technologies in Communication, Education and the Mass Media, with the support of the University Research Institute of Applied Communication (URIAC) of the Faculty of Communication and Media Studies of the University of Athens. The Milia platform aims to support the representation, presentation and collaborative creation of any sort of stories in digital format. Applications of the platform can be found in storytelling per se, in education, in publishing and, more generally, in the creation and publication of collaborative digital works. The first part of the paper is focused on a state of the art review for digital storytelling platforms and discussion of some major challenges that these platforms are attempting to face. This review is followed by a second part, which discusses the technical features and functional capabilities of the Milia platform in detail, and a third part, which reports on applications of the platform that have already been realized and digital stories that are already available online. The paper is concluded with a discussion of limitations and directions of future work for the Milia platform.